Torsional behavior of RC beams strengthened with PBO-FRCM composite – An experimental study. (1st April 2017) - Alabdulhady, Meyyada Y.; Sneed, Lesley H.; Carloni, Christian
Highlights: RC beams were strengthened with PBO-FRCM composite and tested under torsion. Behavior was investigated in terms of strength, rotational ductility, failure mode. Strains measured in the internal and external reinforcement were evaluated. Analytical prediction was compared with the experimental results. Effectiveness of PBO-FRCM composite was compared with CFRP and GFRP composites. Abstract: The use of fiber reinforced cementitious matrix (FRCM) composites has been studied for flexural and shear strengthening of reinforced concrete (RC) members, but currently there are no studies on its use for torsional strengthening. This paper presents the results of an experimental study in which solid rectangular RC beams were externally strengthened with PBO-FRCM composite material in different wrapping configurations to investigate the torsional behavior in terms of strength, rotational ductility, and failure mode. Increases in the cracking torque, torsional strength, and corresponding values of twist were achieved by beams strengthened with a 4-sided wrapping configuration relative to the control (unstrengthened) beam. On the other hand, the 3-sided wrapping configuration was found to be largely ineffective in improving the torsional performance due to excessive fiber slippage. The contribution of the strengthening system to the torsional strength was reasonably predicted (±20%) by the strain measured in the composite fibers. Provisions used to estimate the torsional strength of RC beams with fully-wrapped, externally-bonded fiber reinforced polymer (FRP) composites were found to be applicable to beams strengthened with PBO-FRCM composite.